Analysis of the Main Obstacles in the Process of Language Environment Formation from Vygotsky's Perspective and Alternative Solutions Offered to Overcome Them - Falah, Nasrul; Taufiqurrochman, R.; Hasaniyah, Nur (Mauriduna: Journal of Islamic Studies, 2025)
This study aims to identify the main obstacles in creating an Arabic language environment and to discover solutions to them in light of Vygotsky’s theory. The approach used in this study is qualitative. The researcher collected data from various sources and employed multiple tools for data collection, including interviews, observations, and document reviews. The researcher obtained the following results: by adopting Vygotsky’s theory, especially the concepts of the Zone of Proximal Development (ZPD), scaffolding, and the importance of social interaction, this study identified appropriate solutions to overcome these challenges, including: (1). The limited use of Arabic in students’ daily lives. (2). The lack of interaction with native Arabic speakers. (3). The diverse motivations of students in learning Arabic. (4). Difficulties in understanding Arabic structure and grammar. The proposed solutions to address these challenges include: (1). Scaffolding – teachers should provide gradual guidance by applying Arabic grammar in speech and requiring its use in certain situations, such as classrooms and all institute activities. (2). Zone of Proximal Development (ZPD) – applying role-play methods, where students practice becoming speakers in contexts such as interviews, presentations, or conversations in a communication style similar to native speakers. (3). Zone of Proximal Development (ZPD) – forming small study groups, where students with better understanding guide those still in the early stages of learning, thereby increasing motivation through interaction with more proficient peers. (4). Social interaction – employing discussion-based learning methods, such as Q&A among students and practical exercises in the form of conversations to strengthen their understanding of Arabic grammar. The application of the ZPD concept allows students to develop their Arabic language skills through guidance from teachers or more competent peers. At the same time, scaffolding provides gradual support until students can use the language independently. Moreover, social interaction is considered a key element in forming an effective language environment.